2001
DOI: 10.1001/jama.285.16.2114
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors and Adverse Drug Events in Pediatric Inpatients

Abstract: Medication errors are common in pediatric inpatient settings, and further efforts are needed to reduce them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

56
1,231
16
62

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 1,686 publications
(1,365 citation statements)
references
References 22 publications
56
1,231
16
62
Order By: Relevance
“…Iatrogenic disease is a serious problem with a great social impact. It occurs very frequently, is expensive [3][4][5][6][7][8][12][13][14][15][16], and is potentially responsible for high morbidity and mortality [5,6,8,[12][13][14]17,18]. In the U.S., it is estimated that iatrogenic causes are responsible for 225,000 deaths each year, thus being the third leading cause of death after heart disease and cancer [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Iatrogenic disease is a serious problem with a great social impact. It occurs very frequently, is expensive [3][4][5][6][7][8][12][13][14][15][16], and is potentially responsible for high morbidity and mortality [5,6,8,[12][13][14]17,18]. In the U.S., it is estimated that iatrogenic causes are responsible for 225,000 deaths each year, thus being the third leading cause of death after heart disease and cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic events are also an important cause of admission to intensive care units (ICUs) [23][24][25][26][27] and of hospital readmission [28,29]. Little epidemiological data is available [6,10]. However, the few studies that are available have shown that there are some important predictors for the occurrence of iatrogenic events, namely, older age [10,11,14,[18][19][20][21], longer hospital stay [5,10,15,[18][19][20][21], number of drugs taken daily [11,15,18,21,32], associated pathologies [21], poor general medical status on admission [19], associated renal function impairment or failure [18], and IV catheterization [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Electronic physician order entry with real-time practice guidance 16,17 represents the best long term solution for neonatal PN order design to reduce errors and risk of injury to VLBW infants. 18,19 VLBW infants receiving intravenous PN were identified by Kaushal et al 20 as one of the highest risk groups for medical error related injury because of their multiple complex intravenous infusions, narrow therapeutic range and low tolerance for pharmaceutical errors. Electronic order entry and design can significantly reduce medical errors 21,22 and improve PN mineral content.…”
Section: Discussionmentioning
confidence: 99%